PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERHA GURU UPT SMPN BONTONUMA NO. 16 KEPULAUAN SELAYAR - Sulis Rifqa Afifah; Irmawati Thahir; Sadriana Ayu (STKIP Pesisir Selatan, 2026)
This study aims to determine how the principal's leadership is, how the teacher's performance is and whether there is an influence of the principal's leadership on the performance of teachers at UPT SMPN Bontonumpa No.16 Selayar Islands. This type of research is quantitative research or expost facto research. The population in this study was 17 teachers at SMPN Bontonumpa No.16 Selayar Islands. The sample in this study was a sampling technique where all populations were sampled. Data collection techniques in this study were observation, questionnaires and documentation. The results of this study show that the statistical data analysis of the principal's leadership questionnaire shows that the percentage of the principal's leadership is included in the